Impact of Crystal Size and Morphology on Switchability Characteristics in Pillared-Layer Metal-Organic Framework DUT-8(Ni) - Abylgazina, Leila; Senkovska, Irena; Engemann, Richard; Ehrling, Sebastian; Gorelik, Tatiana E.; Kavoosi, Negar; Kaiser, Ute; Kaskel, Stefan (Frontiers in Chemistry, 2021)
Variation of the crystallite size in flexible porous coordination polymers can significantly influence or even drastically change the flexibility characteristics. The impact of crystal morphology, however, on the dynamic properties of flexible MOFs is poorly investigated so far. In the present work we systematically modulated the particle size of a model gate pressure MOF (DUT-8(Ni), Ni2(2,6-ndc)2(dabco), 2,6-ndc - 2,6-naphthalenedicarboxylate, dabco - 1,4-diazabicyclo[2.2.2]octane) and investigated the influence of the aspect ratio, length, and width of anisotropically shaped crystals on the gate opening characteristics. DUT-8 is a member of the pillared-layer MOF family, showing reversible structural transition i.a. upon nitrogen physisorption at 77 K. The framework crystalizes as a rod-like shaped crystals in conventional synthesis. To understand, which particular crystal surfaces dominate the phenomena observed, crystals similar in size and differing in morphology were involved into systematic study. The analysis of the data shows, that the width of the rods (corresponding to the crystallographic directions along the layer) represents a critical parameter governing the dynamic properties upon adsorption of nitrogen at 77 K. This observation is related to the anisotropy of the channel like pore system and the nucleation mechanism of the solid-solid phase transition triggered by gas adsorption.